Unpacking the interaction between foreign language learners’ emotion, cognition, and activity in the flipped classroom in higher education: A perezhivanie perspective - Qin, Lili; Yao, Lan; Jin, Yinxing (Frontiers in Psychology, 2022)
Few studies have investigated learners’ emotional experiences and the interactions between emotion, cognition, and action in the flipped foreign language classroom (i.e., a mixed teaching mode that combines in-class teaching and off-class self-directed learning). This study addressed these research gaps by exercising a longitudinal narrative study on a total of 32 Chinese-as-the-first-language university students of English who attended a 15-week English course with this teaching design. The results showed that the participants experienced more of positive emotions than negative emotions in this teaching context. Complex interactions between emotion, cognition, and action were revealed, but generally (negative) positive emotion, cognition, and action were interconnected. The findings show that in general learners experienced more positive emotions due to the dynamic, developmental and historical mediators .